“Trastorno por déficit de atención con hiperactividad: Integración social en la convivencia escolar” . - Abata Pilatasig, Diego Adrian (2024)
The research work is aimed at investigating the problems that are created in the educational field due to the condition of Attention Deficit Hyperactivity Disorder (ADHD). Starting from the objective of this research, which is to explain the repercussions that children diagnosed with Attention Deficit Hyperactivity Disorder have in the field of social integration and school coexistence, this in order to help reduce levels of isolation and discrimination towards the learners. The methodology has a qualitative approach, the type of research used is bibliographic, through a comparative method the differences that exist between children with and without ADHD have been indicated. The results obtained through the search for information found in books, articles, magazines and websites, it is determined that ADHD exists from childhood and lasts until adulthood on a global scale, this condition significantly affects the process of social integration. and conceiving great repercussions from the school level. Concluding, ADHD is a condition that can be diagnosed and treated, however, the lack of knowledge of this condition on the part of family members and teachers affects the social integration of the infant from the first years of life, becoming more relevant and complex in the future. as the child acquires self-knowledge of his or her condition.